1995
DOI: 10.1007/bf02537038
|View full text |Cite
|
Sign up to set email alerts
|

Thermal acclimation and dietary lipids alter the composition, but not fluidity, of trout sperm plasma membrane

Abstract: The effect of a long-term adaptation of rainbow trout to 8 and 18 degrees C combined with a corn oil- or a fish oil-supplemented diet on the characteristics of the spermatozoan plasma membrane was investigated. The experiment lasted up to 22 mon during which spermatozoa were collected from the mature males. Spermatozoan plasma membranes were isolated by nitrogen cavitation, and the cholesterol content, phospholipid composition and fatty acid pattern were investigated. Membrane viscosity was assessed on whole c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 55 publications
4
53
0
2
Order By: Relevance
“…Labbé et al (1995) also observed the maintenance of a specific level of some PUFAs in sperm membranes of trout. In our opinion, supplying an adequate diet is vital for the animal, as this will allow making the metabolic effort required to obtain the essential PUFA proportion needed in the sperm.…”
Section: Fatty Acids In Broodstock Dietsmentioning
confidence: 78%
See 4 more Smart Citations
“…Labbé et al (1995) also observed the maintenance of a specific level of some PUFAs in sperm membranes of trout. In our opinion, supplying an adequate diet is vital for the animal, as this will allow making the metabolic effort required to obtain the essential PUFA proportion needed in the sperm.…”
Section: Fatty Acids In Broodstock Dietsmentioning
confidence: 78%
“…The conservation of ARA and EPA levels may have a physiological significance, whereas the constant levels of DHA may have a structural one. In fish, high proportions of DHA have been found in sperm (Bell et al, 1996;Labbé et al, 1993Labbé et al, , 1995Pérez et al, 2000Pérez et al, , 2007Pustowka et al, 2000) indicating it has an important structural function. DHA maximizes transport of electrons in the mitochondria leading to increased energy output (Valentine and Valentine, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations